Dietary acculturation and changes of Central Asian immigrant workers in South Korea by health perception - Lee, EunJung; Kim, Juyeon (Journal of nutrition and health, 2021)
Purpose: This study analyzed the dietary patterns of Central Asian immigrant workers (Mongolia, Kazakhstan, Uzbekistan, and Kyrgyzstan) living in South Korea to determine the food acculturation and how their dietary practices have changed after immigration. Methods: Self-administered questionnaires were completed by 186 Central Asian immigrant workers living in South Korea. A food frequency questionnaire (FFQ) was used to obtain information on the consumption frequency of 22 food items before and after their immigration to Korea. Results: Central Asians switched to Korean meat consumption patterns, which consume mainly pork, chicken, and beef, showing a decrease in the intake of beef and lamb and an increase in that of pork. Their consumption of Namul (cooked vegetable), Kimchi, rice, and marine products increased while that of potatoes decreased during acculturation to Korean food culture. Positive changes were observed in Mongolians’ eating habits. Their meat-based diet turned into a healthy one in which nutritional balance was achieved by consuming the various food groups. Negative dietary changes were also observed; intake of instant foods and coffee increased while black and green tea consumption decreased. Intake of Namul (p < 0.01), Kimchi (p < 0.01), rice (p < 0.001), ramen (p < 0.001), pork, chicken (p < 0.01), fish (p < 0.01), seafood (p < 0.001), and coffee (p < 0.001) increased significantly in the group that responded and their health improved after moving to Korea. This result suggests that health improved among those who were well settled in Korea and ate the various food groups. Conclusion: These findings can help understand the acculturation process to Korean food culture and provide a basis for developing policies to help them adjust to Korean food culture. KCI Citation Count: 0